Pragmatic Analysis on Deixis to Short Story of “What the Old Man Does is Always Right” - Khairun Niswa (Journal of English Language and Education, 2021)
Language is a system to communicate with people around us. One branch of language is pragmatic. Pragmatic is the study of contextual meaning. Contextual meaning is getting from language use or relation of language and context. Deixis is one of study in pragmatic learn about the relation of language and context. Deixis or deictic expression is an expression to indicate to the participant, time, place, discourse and social status. The aims of this research are to found types of deixis and the dominant type used in “What the old man does is always right” written by Hans Christian Andersen in 1930. The story was taken from the internet website of http://hca.gilead.org.il/old_man.html. The source of data is that short story and the data is the word in that story point to types of deixis. This research used Levinson theory in categorized types of deixis. Types of deixis based on Levinson theory are person deixis, place deixis, time deixis, discourse deixis and social deixis. This research used descriptive qualitative method because the data analyzed in word form and explain the data descriptively. The data analyzed step are read the whole text, classified and analyzed based on the theory. The findings of this research are short story used five types of deixis and the dominant type used is person deixis (77.95%). The other types of deixis are time deixis (4.41%), place deixis (4.04%), discourse deixis (9.92%), and social deixis (3.68%). Deixis or deictic expression needed to have more understanding in read short story “What the old man does is always right”.